Impact of Middle East Conflict on Financial Performance of Contractor Firms Listed on the Indonesia Stock Exchange - Grace citra dewi; Amir; Irhamsyah (Cita konsultindo, 2026)
This study examines the impact of the Middle East conflict on the financial performance of contractor companies listed on the Indonesia Stock Exchange (IDX). Escalating geopolitical tensions in the Middle East have contributed to rising energy prices, supply chain disruptions, and increased global financial uncertainty, which may indirectly influence firm-level profitability, particularly in capital-intensive sectors such as construction. This research aims to analyze the effect of internal financial indicators Cash Ratio, Debt to Asset Ratio (DAR), Firm Size, and Inventory Turnover on Return on Assets (ROA) within the context of geopolitical instability. Using a quantitative research design, this study employs panel data derived from the annual financial statements of contractor companies listed on the IDX during the observation period. Multiple regression analysis is utilized to examine both the partial and simultaneous effects of liquidity, leverage, firm size, and operational efficiency on profitability. The findings indicate that internal financial characteristics significantly influence ROA. Liquidity plays an important role in maintaining operational stability, although excessive cash holdings may reduce asset efficiency. Leverage is found to increase financial vulnerability during periods of uncertainty, while larger firms demonstrate greater resilience due to stronger access to capital and diversified operations. Inventory turnover also contributes to profitability by reflecting operational efficiency, although it may be affected by global supply chain disruptions. This study contributes to the literature by integrating external geopolitical risk considerations with firm-level financial ratio analysis in an emerging market context. The results provide practical implications for corporate managers, investors, and policymakers in formulating financial strategies to enhance resilience against global geopolitical instability, particularly within the construction sector.